The concept of improving communication in BIM during transfer to operation phase on the Polish market. (2017) - Dubas, Sebastian; Pasławski, Jerzy
Abstract: Communication problem in construction industry is an important matter due to its direct influence on quality of works. Digital support such as BIM software could help in increasing transfer of information between parties. Authors noticed a need for solution to streamline collaboration between stakeholders at a final stage of the investment. Customer at the construction site, is not involved in the construction process until handover. However, he is the one responsible for acceptance of the construction works by signing the final acceptance protocol and verifying whether works have been done according to contract and variations. Due to defects occurring as a result of construction works and nonconformity with variation order or original design, authors suggest creating a program to simplify communication and improve the exchange of information limited not only to construction, but also during the transition phase between the final stage of construction works and the initial stage of operation of the facility. Case study was conducted to reveal the actual digitalization level of recording final works inspection protocol and defect management system at housing construction sector in Poland.